PHASE TRANSFORMATION OF CASO4 GRANULES TO CACO3 GRANULES BY DISSOLUTION–PRECIPITATION REACTION WITH 12 HOURS IMMERSION TIME - Difa Putri Utami; Decky Joesiana Indrani; Bambang Irawan; Sunarso Sunarso (FKG Unlam, 2019)
Background: Synthetic bone graft is a material that resembles human bone phase and is developed due to clinical demand. Calcium carbonte (CaCO3/Calcite) has been used as bone substitution one of the methods to fabricate calcite is phase transformation by dissolution–precipitation reaction. Previous study did the same method but with lower temperature (<100ºC). Calcium sulfate anhydrate (CaSO4) granules used as precursor is immersed in 0.5 mol/L sodium carbonate (Na2CO3) solution at 100ºC for 12 h. Objective: This study aims to fabricate CaCO3 granules from CaSO4 granules when the temperature is higher than the previous study. Methods: Fabricate CaCO3 granules using CaSO4 granules as precursor by dissolution-precipitation reaction in Na2CO3 solution with 12 h immersion time with 100ºC temperature. Powder X-ray diffraction patterns and Fourier transform infrared spectra study will be performed to characterize the granules. Results: CaCO3 granules are fabricated by dissolution-precipitation reaction in Na2CO3 solution with 12 h immersion time when the temperature was 100ºC. Conclusion: CaSO4 granules used as precursor are a potential material to fabricate CaCO3 by using dissolution-precipitation reaction with 12 hours immersion time and 100ºC temperature.